Role of Excess Inorganic Pyrophosphate in Primer-Extension Genotyping Assays - Xiao, Ming; Phong, Angie; Lum, Kristen L.; Greene, Richard A.; Buzby, Philip R.; Kwok, Pui-Yan

(untitled) (Genome Research, 2004)
We have developed and genotyped >15,000 SNP assays by using a primer extension genotyping assay with fluorescence polarization (FP) detection. Although the 80% success rate of this assay is similar to those of other SNP genotyping assays, we wanted to determine the reasons for the failures and find ways to improve the assay. We observed that the failed assays fell into three general patterns: PCR failure, excess of heterozygous genotypes, and loss of FP signal for one of the dye labels. After analyzing several hundred failed assays, we concluded that 5% of the assays had PCR failure and had to be redesigned. We also discovered that the other two categories of failures were due to misincorporation of one of the dye-terminators during the primer extension reaction as a result of primer shortening with a reverse reaction involving inorganic pyrophosphate, and to the quenching of R110-terminator after its incorporation onto the SNP primer. The relatively slow incorporation of R110 acycloterminators by AcycloPol compounds the problem with the R110 label. In this report, we describe the source of the problems and simple ways to correct these problems by adding pyrophosphatase, using quenching as part of the analysis, and replacing R110 by Texas red as one of the dye labels. With this new protocol, we have achieved ∼95% success rate in assay development without the need for optimization.